Tryptophan in banana peel (Musa paradisiaca) as an anti-dementia alternative treatment: A narrative review - Daffara Kinanthi Lustikaiswi; Sapto Yuliani; Rahmah Annura; Elmi Rahmadani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
As the prevalence of dementia increases from year to year, the discovery and invention of preventive measures are growing increasingly urgent. Banana peels contain tryptophan, an amino acid that plays a substantial role in the mechanism of dementia prevention, yet under-utilized for this purpose. Tryptophan acts as a precursor to serotonin and kynurenine. The serotonin metabolite, 5-hydroxyindoleacetate or 5-hydroxyindoleacetic acid (5-HIAA), can degrade amyloid-ß (Aß) oligomers, a peptide group of 36–43 amino acids derived from amyloid precursor protein found in people with Alzheimer's disease. The degradation of brain cells through the increase of neprilysin (NEP) and melatonin inhibits glycogen synthase kinase-3ß (GSK3ß) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-?ß) by reducing the decrease in peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 (Pin1). Meanwhile, in the kynurenine pathway, kynurenic acid (KYNA) also induces the NEP gene, thus preventing Aß.